General Description Of The History Of Urbanization Processes Of Southern Cities (Eurasian Journal of History, Geography and Economics, 2024)
Urbanization processes are directly related to the development, advancement and rise of society, and on their basis there are historical foundations related to the emergence and development of cities, their socio-economic and cultural-political life. Under the influence of urbanization processes, the increase in the weight of cities and urban population in individual regions and countries serves as the basis. From this point of view, in general, urbanization in Uzbekistan also has its own historical stages of development, on its basis there are both ancient cities and cities founded in the second half of the 20th century.